L’écriture poétique de la Chine chez Shan Sa - DAROUI, Maroua (Journal of Human Sciences, 2016)
The Naked Zither is the last novel by Shan Sa written in French. Chinese origin and French by adoption, she always tries to tell about her country highlighting the poeticity of her text that distinguishes her from the other writers of her time. This article will be devoted to the analysis of one aspect of the author’s writing techniques related to the Chinese culture that appears as ethnostylistique and that intends to be a vector for her poetic identity.